Distance learning in the time of Covid-19: Exploring students’ anxiety - Hapsari, Christianti Tri (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Performing sudden and uncertain distance learning can be difficult and complicated experiences for students as they may suffer from anxiety. The study of anxiety in Indonesia typically concentrated on the relation of anxiety with speech production (Anandari, 2015), gender differences (Nurhaeni, 2019), four basic skills (reading, writing, speaking, and listening) (Male, 2018) and its impact on language learning (Budiman, Ngadiso, & Suparno, 2017). The study of anxiety in distance learning especially in the time of crisis, like the outbreak of Covid-19 is rare. Thus, the study to examine the distance learning anxiety faced by higher education students in the time of crisis (Covid-19) and explore the cause of those anxieties is important. The data of this study was collected using two instruments, a questionnaire and an interview. To get the data, the researcher modified the Foreign Language Classroom Anxiety Scale questionnaire (FLCAS) by Howitz and Young (1991) which is commonly applied to determine the level of anxiety. Since the study concentrated in distance learning, the researchers also decided to adopt an Ã¢â‚¬Å“On-line Language Learning Anxiety (OLLA) InventoryÃ¢â‚¬Â (Majid, Othman, & Rahmat, 2007). Findings revealed that students experienced higher anxiety levels in the beginning stage of distance learning. A year after the implementation of distance learning, students had adapted well and the level of anxiety they encountered was reduced. Yet, technical problems like unstable internet connection and devicesÃ¢â‚¬â„¢ malfunction that occurred during distance learning still triggered much anxiety among students since that condition made them lose the opportunity to receive some important information and chances to actively participate in online activities as well as improve their skills.